Antibiotic Consumption and Its Relationship with Bacterial Resistance Profiles in ESKAPE Pathogens in a Peruvian Hospital - Giancarlo Pérez-Lazo; Susan Abarca-Salazar; Renata Lovón; Rocío Rojas; José Ballena-López; Adriana Morales-Moreno; Wilfredo Flores-Paredes; Berenice Arenas-Ramírez; Luis Ricardo Illescas (MDPI AG, 2021)
A descriptive design was carried out studying the correlation between antimicrobial consumption and resistance profiles of ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) in a Peruvian hospital, including the surgical, clinical areas and the intensive care unit (ICU) during the time period between 2015 and 2018. There was a significant correlation between using ceftazidime and the increase of carbapenem-resistant Pseudomonas aeruginosa isolations (R = 0.97; p < 0.05) and the resistance to piperacillin/tazobactam in Enterobacter spp. and ciprofloxacin usage (R = 0.97; p < 0.05) in the medical wards. The Pseudomonas aeruginosa resistance to piperacillin/tazobactam and amikacin in the intensive care unit (ICU) had a significant reduction from 2015 to 2018 (67% vs. 28.6%, 65% vs. 34.9%, p < 0.001). These findings give valuable information about the rates and dynamics in the relationship between antibiotic usage and antimicrobial resistance patterns in a Peruvian hospital and reinforce the need for continuous support and assessment of antimicrobial stewardship strategies, including microbiological indicators and antimicrobial consumption patterns.